A review on 2D MoS2 cocatalysts in photocatalytic H2 production. (1st November 2020) - Liang, Zizhan; Shen, Rongchen; Ng, Yun Hau; Zhang, Peng; Xiang, Quanjun; Li, Xin
Abstract: Owing to their unique physicochemical, optical and electrical properties, two-dimensional (2D) MoS2 cocatalysts have been widely applied in designing and developing highly efficient composite photocatalysts for hydrogen generation under suitable light irradiation. In this review, we first elaborated on the fundamental aspects of 2D MoS2 cocatalysts to include the structural design principles, synthesis strategies, strengths and challenges. Subsequently, we thoroughly highlighted and discussed the modification strategies of 2D MoS2 H2 -evolution cocatalysts, including doping heteroatoms (e.g. metals, non-metals, and co-doping), designing interfacial coupling morphologies, controlling the physical properties (e.g. thickness, size, structural defects or pores), exposing the reactive facets or edge sites, constructing cocatalyst heterojunctions, engineering the interfacial bonds and confinement effects. In the future, the forefront challenges in understanding and in precise controlling of the active sites at molecular level or atomic level should be carefully studied, while various potential mechanisms of photogenerated-electrons interactions should be proposed. The applications of MoS2 cocatalyst in the overall water splitting are also expected. This review may offer new inspiration for designing and constructing novel and efficient MoS2 -based composite photocatalysts for highly efficient photocatalytic hydrogen evolution.